2022
DOI: 10.1177/17455065221076731
|View full text |Cite
|
Sign up to set email alerts
|

Quality of antenatal care and associated factors among pregnant women in East Africa using Demographic and Health Surveys: A multilevel analysis

Abstract: Introduction: Antenatal care offers a forum for critical healthcare functions, including health education, screening, and disease prevention. Several pocket studies carried out in specific localities of East African countries were investigated. However, these were neither representative of the country nor specific to the recommended minimum of four antenatal care visits. Therefore, this study aimed to identify factors associated with quality of antenatal care among pregnant women in East Africa. Methods: A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
8
23
1
Order By: Relevance
“…The odds of receiving all ANC components were six times higher among women who had at least one child, and reduced by half to three times higher among those with two to four children, compared to those with five or more children. This finding is not surprising because it has been reported consistently by studies in Ethiopia [ 45 , 49 ], Haiti [ 50 ], Nigeria [ 51 ], and in an analysis of combined DHS data of six East African countries [ 13 ]. This could be due to the fact that women with multiple parities have a lower desire to continue attending all the recommended ANC visits.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The odds of receiving all ANC components were six times higher among women who had at least one child, and reduced by half to three times higher among those with two to four children, compared to those with five or more children. This finding is not surprising because it has been reported consistently by studies in Ethiopia [ 45 , 49 ], Haiti [ 50 ], Nigeria [ 51 ], and in an analysis of combined DHS data of six East African countries [ 13 ]. This could be due to the fact that women with multiple parities have a lower desire to continue attending all the recommended ANC visits.…”
Section: Discussionsupporting
confidence: 65%
“…Although still very low, at 13.1%, this proportion of women who utilized all ANC components in Rwanda represents a significant increase from the 1.9% of the 2015 RDHS [ 12 ]. It is slightly higher than the East African region prevalence of 11% [ 13 ]. In 2019, Benova et al, analyzed DHS data from 10 LMICs’s, which showed that Rwanda’s current proportion of women receiving all ANC components is higher than Nigeria’s (6.7%), close to that of Democratic Republic of Congo (12.6%) and lower than that of Zambia (21.8%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations